Synthesis of NaY(MoO4)2 single crystals from molybdate-fluoride melts - Terebilenko, K.V.; Kyselov, D.V.; Odynets, I.V.; Slobodyanik, M. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
The crystallization trends in the molten system Na−Y−Mo−O−F have been studied, and two crystallization fields of the compound NaY(MoO4)2 and NaY(MoO4)2+Na5Y(MoO4)4 mixture are defined. The synthesis of NaY(MoO4)2 in molybdate-fluoride melts at the YF3 content 10% (mol) and ratios Na/F = 1.0−1.2; Na/Mo = 0.5−0.7 was performed for the first time. The congruent melting point was found at 549 ºC. Interpretation of the results was carried out, by using infrared spectroscopy, X-ray powder diffraction, and DTA analysis.